HUBUNGAN PENGALAMAN MENYUSUI DAN SUMBER INFORMASI IBU, TERHADAP PENGETAHUAN IBU DALAM MEMBERIKAN AIR SUSU IBU (ASI) PADA BAYI BERAT LAHIR RENDAH (BBLR) DI RSUD H.ABDUL MOELOEK BANDAR LAMPUNG - Elsy Juni Andri Kariny; Fatmah Indriana Fuaida; Nadya Dwita Fatma Sari (Rena Cipta Mandiri, 2026)
Background: Indonesia had the highest infant mortality rate (IMR) among all ASEAN countries in 2015, at 22.23 per 1,000 live births, with the main cause being low birth weight (LBW). One treatment to reduce IMR caused by LBW is through breastfeeding (ASI). Objective: To determine the relationship between maternal age and mothers’ knowledge in providing breast milk (ASI) to infants with LBW at RSUD Dr. H. Abdul Moeloek, Bandar Lampung. Method: Posttest-Only Control Design method. Population: mothers with LBW infants. Sample: 42 respondents. Instrument: breastfeeding questionnaire. Analysis: Chi-Square. Results: The variable of breastfeeding experience among mothers showed a significant relationship with mothers’ knowledge in providing breast milk (p = 0.002), while the information variable showed no significant relationship with mothers’ knowledge (p > 0.08). Conclusion: There is a relationship between maternal age and mothers’ knowledge in providing breast milk (ASI) to LBW infants.